Design for service life of underground space based on water seepage criterion. (November 2019) - Yang, Wei; Li, Chun-Qing; Baji, Hassan
Highlights: A method for design of service life of underground space is proposed. A stochastic model of water seepage depth in concrete lining is developed. The method allows for the nature of randomness and time variance of design variables. The correlation of seepage depth between two points in time affects the probability of water seepage. Abstract: Ever increased urbanisation in the world has made the underground space a viable alternative to the expanding city space. Underground space usually operates under the water level whereby the water ingress is one of the most detrimental factors affecting its service life and sustainability. But little or no research has been conducted on design for service life of underground space based on the criterion of water seepage. This paper proposes a rational and practical methodology for design of service life of underground space as represented by its lining structures against water seepage. A stochastic model of water seepage depth in concrete lining is developed. The proposed methodology is verified with numerical method for prediction of the probability of failure due to water seepage. The merit of the proposed methodology is that it allows for the randomness and time variation of design variables and also directly relates to the real time in service of underground space. It is found in the paper that the correlation of water seepage depth between two points in time and the concrete constituent materials can significantly affect the probability of water seepage failure. The significance of the proposed methodology is that it can be used as a design guide for service life of underground space based on various design criteria.